What is known and unknown about the effects of plastic pollution: A meta-analysis and systematic review - Bucci, K.; Tulio, M.; Rochman, C. M. (Ecological applications, 2020)
As a consequence of the global ubiquity of plastic pollution, scientists, decisionmakers, and the public often ask whether macroplastics (>5 mm) and microplastics (< mm) have a realized ecological threat. In 2016, we conducted a systematic review of the literature and made a call for further research testing hypotheses about ecological effects. In the subsequent years, the amount of relevant research has risen tremendously. Here, we reassess the literature to determine the current weight of evidence about the effects of plastic pollution across all levels of biological organization. Our data spans marine, freshwater, and terrestrial environments. We extracted data from 139 lab and field studies testing 577 independent effects across a variety of taxa and with various types, sizes, and shapes of plastic. Overall, 59% of the tested effects were detected. Of these, 58% were due to microplastics and 42% were due to macroplastics. Of the effects that were not detected, 94% were from microplastics and 6% were from macroplastics. We found evidence that whether or not an effect is detected, as well as the severity and direction of the effect, is driven by dose, particle shape, polymer type, and particle size. Based on our analyses, there is no doubt that macroplastics are causing ecological effects, however, the effects of microplastics are much more complex. We also assessed the environmental relevancy of experimental studies by comparing the doses used in each exposure to the concentrations and sizes of microplastics found in the environment. We determined that only 17% of the concentrations used in experimental studies have been found in nature, and that 80% of particle sizes used in experiments fall below the size range of the majority of environmental sampling. Based on our systematic review and meta-analysis, we make a call for future work that recognizes the complexity of microplastics and designs tests to better understand how different types, sizes, shapes, doses, and exposure durations affect wildlife. We also call for more ecologically and environmentally relevant studies, particularly in freshwater and terrestrial environments.